Comparation of Antihypertensive Effect of Goldenberry, Cucumber, and Combination Juice Against Systolic Blood Pressure on Rats Induced 8% NaCl - Husna, Fiki; Damayanti, Amilia Yuni; Sari, Dianti Desita (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2019)
This study was a true experimental study using the randomized controlled group method with a pre-post test design. The Sprague-Dawley rats were divided into 4 groups (5 rats/group): K (+) Captopril 0,45 mg/200 g BW, goldenberry juice 1,8 ml/200 g BW (P1), cucumber juice 1,8 ml/200 g BW (P2), and 1,8 ml/200 g BW (P3, combination juice 50%:50%). Systolic blood pressure measured by blood pressure analyzer with the tail-cuff method. The result of systolic blood pressure analyzed by Paired t-Test to determine the mean difference of systolic blood pressure before and after 8% NaCl induction. One Way ANOVA test followed by Post Hoc Duncan to determine the mean difference of systolic blood pressure between groups. Goldenberry, cucumber, and combination juice have a significant effect of reducing systolic blood pressure in hypertension with p = 0,000 (<0,05). Goldenberry juice was the most effectively on reducing systolic blood pressure in hypertension with 42.21%.